Epilepsy Surgery in Children - Faraji, M.; Ashrafzadeh, F.; Faraji rad, S. (Iranian Journal of Child Neurology, 2009)
Objective In the majority of patients with intractable epilepsy, seizures can be well controlled with appropriate medication. However, current estimates indicate that some of patients with epilepsy are refractory to all forms of medical therapy. The surgical treatment of intractable epilepsy in children has evolved with advances in technical innovations. These medically intractable patients are candidates for surgical treatment in an attempt to achieve better seizure control. The definitive successful outcome of epilepsy surgery is a seizure-free state without significant neurological impairments. In this article, we will outline the essential elements of presurgical evaluation and describe a variety of therapeutic surgical options, and the related indications, techniques, results and complications of each procedure.